2013
DOI: 10.1097/aap.0b013e31828db12f
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasound-Guided Popliteal Block Through a Common Paraneural Sheath Versus Conventional Injection

Abstract: An ultrasound-guided popliteal sciatic nerve block through a common paraneural sheath at the site of sciatic nerve bifurcation is a simple, safe, and highly effective block technique. It results in consistently short onset time, while respecting the integrity of the epineurium and intraneural structures.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
75
2
7

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 88 publications
(87 citation statements)
references
References 13 publications
3
75
2
7
Order By: Relevance
“…These authors observed that the subparaneural technique resulted in a higher success rate (84% vs 56%; p=0.032) as well as improved efficiency (decreased performance/onset/total anesthesia-related times and fewer needle passes). Tran et al ’s initial findings were reproduced by Perlas et al 197 Using a similar research hypothesis, LA mix, injectate volume, and assessment scale for sensorimotor block, these authors found that, compared with separate injections around the TN and CPN, the subparaneural technique resulted in a higher incidence of complete block at 30 min (76% vs 49%; p=0.026) as well as a 30% reduction in onset time for sensory and motor block. A third trial (n=48) compared subparaneural to supraparaneural LA injection at the sciatic neural bifurcation 198.…”
Section: Nerve Blocks Of the Sacral Plexusmentioning
confidence: 80%
“…These authors observed that the subparaneural technique resulted in a higher success rate (84% vs 56%; p=0.032) as well as improved efficiency (decreased performance/onset/total anesthesia-related times and fewer needle passes). Tran et al ’s initial findings were reproduced by Perlas et al 197 Using a similar research hypothesis, LA mix, injectate volume, and assessment scale for sensorimotor block, these authors found that, compared with separate injections around the TN and CPN, the subparaneural technique resulted in a higher incidence of complete block at 30 min (76% vs 49%; p=0.026) as well as a 30% reduction in onset time for sensory and motor block. A third trial (n=48) compared subparaneural to supraparaneural LA injection at the sciatic neural bifurcation 198.…”
Section: Nerve Blocks Of the Sacral Plexusmentioning
confidence: 80%
“…[5][6][7] Depending on where the needle tip is inserted and the spread of LA solution, significant differences in onset time and duration of sensory and motor blockades have been reported. [8][9][10][11][12][13] The recent literature highlights the importance of obtaining an extraneural concentric distribution of LA around the sciatic nerve 1,14,15 or an extraneural injection surrounding both tibial and peroneal nerves distal to the bifurcation. 12,13,16 In 2 studies, a proximal injection below the paraneural sheath seemed superior to an extraneural distal injection around both separate tibial and peroneal nerves.…”
mentioning
confidence: 99%
“…Local anesthetic injection within the paraneuracompartment proximal to the sciatic, saphenous or femoral nerve under ultrasound guidance is highly effective in achieving analgesia in comparison to other sites of injection around the nerves and was the universal needle tip localization point in this study [20]. Conventional ultrasound technology allows this localization and this site poses a reduced risk of nerve injury than a subparaneuralor intraepineural injection site that requires high definition imaging processors not readily available in many centers [21].…”
Section: Discussionmentioning
confidence: 99%